Prevalence of Comorbid Conditions with Aging Among Patients with Diabetes and Cardiovascular Disease - Davis, James W (University Clinical, Education & Research Associate (UCERA), 2011)
OBJECTIVES: The objectives were to develop a methodology to understand the prevalence of medically complex patients, and to apply the methodology to examine patients with one or more of hypertension, hyperlipidemia, diabetes, and heart disease. METHODS: Prevalence was measured using insurance data by calculating the proportion of days patients in a health state of interest contributed to the total days of enrollment. Graphs summarized the prevalence patterns within age and morbidity categories. Results by age and gender were supplemented with cubic spline curves that closely fit the prevalence data. RESULTS: The study provides basic epidemiologic information on changes with aging in the prevalence of patients with one or more comorbid conditions. Patients such as those with hyperlipidemia alone rose in prevalence at younger ages and fell at older ages, whereas the prevalence of other patients, such as patients having hypertension, diabetes, and heart disease, progressively increased with age. With straightforward extensions of the methodology other issues such as the incidence of emergency department visits and hospitalizations might be investigated.